NEMI IAQ SERVICES PROGRAM STATUS AND FINANCIAL REPORT FOR THE LABOR MANAGEMENT COMMITTEE (Tufts Archival Research Center, 2007)
Financial report on the indoor air quality program status. Lists several topics related to indoor air quality and then the activies already undertaken and the activities planned for that topic. Concludes with a table of the monthly budget funding ending 5/31/94.